RISE: Erasmus+KA2: the complexities of the creation of a validation protocol for the Making4.0 curriculum between the Malaysian and European education systems / Prof. Dr Shahriman Zainal Abidin - Zainal Abidin, Shahriman (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Recently, the trend in education is rapidly changing due to technological innovation and work demand.